Integration of audio‐visual information for spatial decisions in children and adults. Issue 5 (17th July 2015) - Nardini, Marko; Bales, Jennifer; Mareschal, Denis
Abstract: In adults, decisions based on multisensory information can be faster and/or more accurate than those relying on a single sense. However, this finding varies significantly across development. Here we studied speeded responding to audio‐visual targets, a key multisensory function whose development remains unclear. We found that when judging the locations of targets, children aged 4 to 12 years and adults had faster and less variable response times given auditory and visual information together compared with either alone. Comparison of response time distributions with model predictions indicated that children at all ages were integrating (pooling) sensory information to make decisions but that both the overall speed and the efficiency of sensory integration improved with age. The evidence for pooling comes from comparison with the predictions of Miller's seminal 'race model', as well as with a major recent extension of this model and a comparable 'pooling' (coactivation) model. The findings and analyses can reconcile results from previous audio‐visual studies, in which infants showed speed gains exceeding race model predictions in a spatial orienting task (Neil et al ., 2006) but children below 7 years did not in speeded reaction time tasks (e.g. Barutchu et al ., 2009). Our results provide new evidence for early and sustained abilities to integrate visual and auditory signals for spatial localization from a young age. Abstract : Children aged 4–12 years and adults were faster at localising audio‐visual targets given both senses together compared with either alone. All groups' reaction times were best explained by integration (pooling) of sensory information. These results provide new evidence for early and sustained abilities to integrate visual and auditory signals for spatial localisation from a young age.